Repair and renewal of buildings proceedings of a conference organized by the Institution of Civil Engineers and held in London on 17 November 1982. (Thomas Telford, 1983)
Following on from the opening address by J.V. Bartlett, these papers focus on cladding structure inter-action, structural remedial works for listed buildings and old monuments, engineering the restoration, highlights various stages, and concludes by discussing remedial work to 20th century buildings.